Penyuluhan Peningkatan Kompetensi Siswa SMAN 2 Tapung Dalam Pembuatan Silase Hijauan Pakan Ternak - Jati, Putri Zulia (Institut Teknologi Pendidikan Indonesia, 2024)
The decrease in agricultural land area has an impact on the availability of forage products which have been used by the community as animal feed. Silage is forage that is preserved using fermentation techniques. Fresh preserved forage is produced after the grass undergoes an insilage (fermentation) process assisted by lactic acid bacteria in an acidic and anaerobic atmosphere. Silage is animal food that has a high water content, processed through a fermentation process with the help of microorganisms. This process is carried out under anaerobic conditions or without oxygen, either with or without addition. In an effort to increase and fulfill the nutrients that are lacking in feed, it is necessary to provide additional supplements so that livestock nutrition can be fulfilled. One process that can be used is the silage fermentation process. In principle, making animal feed in the form of silage is like the fermentation process in general. The ingredients used consist of three groups or components of ingredients, namely the forage feed ingredient group which is the main ingredient, the concentrate feed ingredient group, and the additive feed ingredient group. In this way, making silage can increase livestock productivity, therefore it is necessary to carry out outreach to increase the competency of SMAN 2 Tapung students in making forage silage in order to improve the quality of students' soft skills in the livestock business so as to prepare themselves for the world of work.